Customer Ability Readiness and Intention to Purchase Using AI in Tourism and Hospitality Businesses: The Mediating Roles of Trust in AI and Customer Engagement - Al-Romeedy, Bassam; Khairy, Hazem; Baquero, Asier (IGI Global, 2026)
[Resumen no disponible]
The study investigates the impact of customer ability readiness (CAR) on intention to purchase using AI (IPAI) in tourism and hospitality businesses, focusing on the mediating roles of customer trust in AI (TAI) and customer engagement (CE). An online survey was conducted to gather data from customers who have experienced using AI in online flights and hotel booking. The PLS-SEM approach was used to analyze 602 valid responses, which were processed using WarpPLS statistical software 7.0. The findings show that CAR positively affects customers' IPAI, TAI, and CE. In addition, customers' IPAI is positively affected by TAI and CE. Furthermore, the findings found that TAI and CE significantly mediate the CAR→IPAI relationship. The study enhances the Technology Acceptance Model (TAM) by enhancing our understanding of the factors influencing AI adoption in the tourism and hospitality sectors. The study also suggests that tourism and hospitality businesses should focus on improving customer readiness to adopt AI technologies.
Keywords: customer ability readiness; intention to purchase; trust in AI; customer engagement